2011
DOI: 10.1088/1741-2560/8/2/025024
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing flashes of items surrounding targets during calibration of a P300-based brain–computer interface improves performance

Abstract: Since the introduction of the P300 BCI speller by Farwell and Donchin in 1988 speed and accuracy of the system has been significantly improved. Larger electrode montages and various signal processing techniques are responsible for most of the improvement in performance. New presentation paradigms have also led to improvements in bit rate and accuracy (e.g. Townsend et al. 2010). In particular, the checkerboard paradigm for online P300 BCI-based spelling performs well, has started to document what makes for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
(46 reference statements)
0
22
0
1
Order By: Relevance
“…However, while these researches succeeded in improving the reliability of identifying target flashes (Liu et al, 2010;Townsend et al, 2012), there was another method that could further increase the ERP-based BCIs. Some studies were focused on decreasing the interference by reducing the number of adjacent flashes (Frye et al, 2011;Liu et al, 2010;Townsend et al, 2010). But increasing the number of flashes of each trial would reduce the speed of the BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, while these researches succeeded in improving the reliability of identifying target flashes (Liu et al, 2010;Townsend et al, 2012), there was another method that could further increase the ERP-based BCIs. Some studies were focused on decreasing the interference by reducing the number of adjacent flashes (Frye et al, 2011;Liu et al, 2010;Townsend et al, 2010). But increasing the number of flashes of each trial would reduce the speed of the BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2012) reported that N170 and vertex positive potentials (VPP) also improve classification accuracy in a P300 BCI with stimuli that change to faces [33]. In addition to changing characters to faces, other types of changes may also offer advantages over the conventional “flash” approach in P300 BCIs ([25], [34], [35], [36], [37]). …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, BCIs may be the only viable option of restoring independent communication and autonomy for some people who are severely disabled. Considerable effort has been invested in improving signal detection, speed, accuracy, and reliability [511]. However, studies in target populations are far less common [12].…”
Section: Translational Focusmentioning
confidence: 99%